LESSON STUDY STRENGTHENING TRAINING FOR YOUNG LECTURERS TO IMPROVE LECTURE QUALITY - Martono Martono; Hairida Hairida; Erwina Oktavianty*; Reni Marlina; Hemri Yansa (Jurnal Visi Ilmu Pendidikan, 2022)
This article aims to describe the implementation of socialization activities and technical guidance for the implementation of Lesson Study for young lecturers in the Faculty of Teacher Training and Education, Tanjungpura University (University) and to explore information about participants' opinions on the implementation of lesson study in lectures. Opinions were obtained from the stages of socialization and technical guidance on the implementation of the learning quality improvement program through Lesson study. This activity is carried out in two stages. Phase 1 is a field orientation activity carried out by the team, the purpose of this activity is to prepare activities and collect data on young lecturers (CPNS) who are in the teacher training institution at university environment. Phase 2 is a lesson study cycle socialization and technical guidance activity which was carried out in a 4-hour meeting on 27 July 2020 at the teacher training institution University. In this activity, 4 team members as resource persons were present to provide strengthening of lesson study to participants in the socialization and technical guidance, besides that this activity was also attended by 29 participants who were young lecturers in the faculty. With these stages, it is hoped that this community services activity can produce an understanding of sustainable programs for young lecturers in order to improve the quality of professional lecturers and can improve the quality of learning so that it results in increased results and learning processes for students. So that in the end it can build a learning community that affects the improvement of the quality of education.Keyword: Lesson Study, Young Teachers, Community Services